Baltic Hospitality from the Middle Ages to the Twentieth Century Receiving Strangers in Northeastern Europe - Nauman, Sari; Jezierski, Wojtek; Reimann, Christina; Runefelt, Leif (Palgrave Studies in Migration History, 2022)
Reflecting debate around hospitality and the Baltic Sea region, this open access book taps into wider discussions about reception, securitization and xenophobic attitudes towards migrants and strangers. Focusing on coastal and urban areas, the collection presents an overview of the responses of host communities to guests and strangers in the countries surrounding the Baltic Sea, from the early eleventh century to the twentieth. The chapters investigate why and how diverse categories of strangers including migrants, war refugees, prisoners of war, merchants, missionaries and vagrants, were portrayed as threats to local populations or as objects of their charity, shedding light on the current predicament facing many European countries. Emphasizing the Baltic Sea region as a uniquely multi-layered space of intercultural encounter and conflict, this book demonstrates the significance of Northeastern Europe to migration history.